(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes the importance of developing leadership qualities in female students in modern society and the problems encountered in this process and their solutions. Also, it will be shown how to increase the leadership potential of girls through practical solutions such as modern educational methodologies, international cooperation programs, mentoring and networking.